Lymphocyte Proliferation and Nitric Oxide-Producing Activities of Lupeol Isolated From Red Dragon Fruit (Hylocereus polyrhizus) Extract - Sri Wahdaningsih; Subagus Wahyuono; Sugeng Riyanto; Retno Murwanti (Cell and BioPharmaceutical Institute, 2021)
Background: Hylocereus polyrhizus has activities as antimicrobial agent, anti-hypercholesterolemia, anti-diabetic (diabetes mellitus), cardiovascular risk reduction, health supplement, and melanoma cell suppression. The extracts from the peels of H. polyrhizus were able to increase phagocytic ability, cell numbers and leukocytes and to influence relative spleen weights in the formation of body immune system in male rats. The fruit peels contained phenolics, flavonoids, carotenoids, and anthocyanins. This study investigated the active compounds of H. polyrhizus peels, which are able to increase immune system of human body.Materials and method: In vitro assay was applied to examine the active compounds, identified as lupeol, obtained from isolated extract of red dragon fruit for their lymphocyte proliferation and nitric oxide (NO)-producing activities. Lymphocyte proliferation assay was performed with 3-4.5-dimethylthiazol-2-yl)-2.5-diphenyltetrazolium bromide (MTT) method. The cell control was lymphocyte cell suspension in RPMI medium added with phytohaemaglutinine (PHA). The NO measurement was conducted with nitric solvent and Greiss reagent.Results: The ANOVA analysis of the average optical density (OD) of lymphocyte proliferation showed that the addition of isolated lupeol at the concentrations of 6.25, 12.5, 25, 50 and 100 µg/mL were able to improve lymphocyte proliferation and activate the NO production in the rats with treatment of positive control. Conclusion: Isolated lupeol at concentrations of 6.25, 12.5, 25, 50 and 100 µg/mL revealed significant difference with medium control and cell control. It was able to increase effects on lymphocyte proliferation and NO production. Therefore, the lupeol which was isolated might have high potential to be an immunostimulant.Keywords: Hylocereus polyrhizus, lupeol, lymphocyte proliferation, nitric oxide production